CONFLICTS PREVENTION IN TEAM- WORK - Jean de PERSON (Management & Marketing)
Building a trust atmosphere and mobilization in a team or an organizationremains the dream of every manager. This article analyses the internalmechanism of a conflict through life positions diagram in which direction anddominance diagrams appear. The first diagonal, the dominance one, revealsan animal behavior, the latter including both positive aspirations (++ quarter),and also deceptions (-- quarter).Passing over crisis situations requires from managers to outrun, through theirstyle and actions the dominance diagonal and pass to a game with reciprocalgaining (++ quarter), based on trust, that color relations between people andrelease their energy.